Analisa Kelayakan Penerima Program Keluarga Harapan (PKH) Menggunakan Algoritma C4.5 - Tanjung, Muhammad Amirsyah; P, Poningsih; Qurniawan, Hendry (STIKOM Tunas Bangsa Pematangsiantar, 2021)
In overcoming the problem of poverty, the Government implements the Family Hope Program (PKH) which is a program assistance that provides assistance (subsidies) in cash to poor households as long as they meet the requirements set out in the program. The purpose of this study is to determine whether the family is still eligible or not receive the Family Hope Program (PKH) assistance, where there are many other disadvantaged families who have not had the opportunity to receive this assistance program. Sources of data obtained from the Martoba Village Head Office. The method used in the study is a data mining technique with the C4.5 algorithm which is implemented with the RapidMiner application. The attributes used in determining the family's eligibility are still feasible or not receiving assistance from this assistance program, namely income, number of family dependents, vehicle ownership and residence status. The results of the classification algorithm C4.5 and testing with Rapid Miner software, it is found that the factor that most influences the eligibility of the Family Hope Program (PKH) recipients is the number of stages (C1) with an acquisition value of 0.51827179